PENGEMBANGAN MEDIA PAPAN INTERAKSI MANUSIA PADA PEMBELAJARAN TEMATIK KELAS V SDN MADUSARI 3 PRAMBANAN SLEMAN - Risa Yuliana; Heri Maria Zulfiati (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
The aim of the research is to produce learning media â€œhuman board interactionâ€ on the thematic learning of fifth grade of SDN Madusari 3 Prambanan, Sleman. Based on the description of the theory and the mindset, the hypothesis in this study is human interaction board media proper to use as a media in the thematic learning which is charged with social science, and be able to create pleasant learning atmosphere otherwise be able to increase the active participation of the learners. The research used to research and development using a development research model by Borg and Gall. The development of the procedure consists of 9 stages are research and data collection, planning, development of initial produce, an initial field trial, product revision, an operation field trial, and final product revision. The population of the research is all of the students of fifth grade SDN Madusari 3 Prambanan Sleman which amount 22 students. The research sample covers the entire population. The researcher used data collection techniques by a questionnaire, observation, and interview with the teacher and the students to find out the situation during the learning process. The data analysis technique used quantitative descriptive statistics. The result shows that the media is proper to use. This is based on the percentage obtained from the learner validator. The percentage of material validator results from lecturer is 80%, worthy of use, the percentage of validation result from the teacher is 83,33%, worthy of use. The percentage of validation results from the lecturer is 77,33%, worthy of use. The percentage of validation results from the teacher is 82,66, worthy of use. The percentage of student evaluations obtained during limited testing is 93% worthy of use. During the field trial 94%, worthy of use. In the operational field, trials produce a percentage value of 94% worth of use.